Internet-delivered cognitive behaviour therapy for university students: Preference trial for various course durations - V. Peynenburg; R.P. Sapkota; N. Titov; B.F. Dear; H.D. Hadjistavropoulos (Internet Interventions, 2025)
Background: Internet-delivered cognitive behaviour therapy (ICBT) is an accessible and effective treatment option for post-secondary students, but engagement and completion rates are less favourable than in non-student populations in routine care. Studies on students' treatment preferences suggest that a range of options should be offered. Examining students' engagement and outcomes associated with ICBT course options of varying durations can help inform how to optimally deliver ICBT to university students in routine care. Methods: University students (N = 72) were offered a choice of a transdiagnostic ICBT course of three different durations (i.e., ultra-brief with no time locks, brief, or standard-length). The trial examined course preferences, predictors of preferences, treatment outcomes (depression, anxiety, and perceived academic functioning) at post-treatment and 4-month follow-up, as well as treatment engagement and satisfaction across course options. Results: Of the 72 students who started treatment, 32 (44.4 %) chose the brief course, 36 (50.0 %) chose standard-length, and 4 (5.6 %) chose the ultra-brief course. Between-group comparisons focused on the brief and standard-length courses, as uptake was too low for the ultra-brief course. From pre-treatment to post-treatment, clients in both groups experienced large reductions in depression (brief: d = 1.26, 95 % CI [0.84, 1.69]; standard: d = 1.43, 95 % CI [0.88, 1.98]) and anxiety (brief: d = 1.40, 95 % CI [0.96, 1.84]; standard: d = 1.59, 95 % CI [1.03, 2.15]), and small but not significant improvements in perceived academic functioning (brief: d = 0.27, 95 % CI [−0.12, 0.67]; standard: d = 0.44, 95 % CI [−0.07, 0.95]). At 4-month follow-up, improvements in depression and anxiety were maintained and improvements in perceived academic functioning reached significance in both groups, with medium effects found. There were no pre-treatment between-group differences in demographic or clinical characteristics and treatment satisfaction was comparable between the groups. The percentage of clients who accessed all lessons was similar in the brief (59.4 %) and standard (55.6 %) courses. Conclusions: As the brief and standard-length course options had similar uptake, outcomes, completion rates, and client satisfaction and similar costs in terms of therapist resources, clinics can confidently offer these options and accommodate student preferences. The low interest in an ultra-brief course prevented evaluation of the outcomes of this course but implies allocating time and resources to offering this option when offered alongside other options is not worthwhile in this particular clinic. Further research could explore whether offering ultra-brief ICBT under different circumstances is of interest and benefit to students.